A study of the carbon distribution in bainitic ferrite. (February 2023) - Pushkareva, Irina; Macchi, Juan; Shalchi-Amirkhiz, Babak; Fazeli, Fateh; Geandier, Guillaume; Danoix, Frederic; Teixeira, Julien Da Costa; Allain, Sébastien Yves Pierre; Scott, Colin
Abstract: The carbon distribution in bainitic ferrite (BF) of two carbide-free bainite alloys isothermally transformed at three different temperatures was studied using a unique combination of in-situ high energy X-ray diffraction (HEXRD), atom probe tomography (APT) and electron energy loss spectroscopy (EELS). Results from all three techniques are consistent and unambiguously confirm the presence of significant excess carbon levels in BF, even in these low nominal carbon (0.22 wt.%) steels. The carbon concentration in BF decreases as the transformation temperature increases, but remains significant up to 430 °C. Further, statistical analysis indicates that the excess carbon content does not follow a normal distribution. APT reconstructions suggest that much (but not all) of the excess carbon is segregated to defects or clusters. No clear evidence for bainite tetragonality was observed. Surprisingly, the addition of a strong carbide forming element (vanadium) in solid solution did not influence the carbon distribution in BF. Graphical abstract: Image, graphical abstract